So what is Capital in the Twenty-First Century? Some notes on Piketty’s book - Kornai, János (Journal of Public Governance, 2016)
According to János Kornai, despite the undeniable original contribution of Capital in the Twenty-First Century, its author offers a partial and distorted analysis of the functioning of the capitalist system, which leads him to mistaken conclusions and to a very limited repertoire of recommendations for politicians. The Hungarian economist criticizes Thomas Piketty particularly for the omission of such aspects as the dynamics of capitalism, competition as a stimulus to act, technical progress and its impact on all aspects of modern human life. He illustrates his views with numerous examples taken from the work of other economists.